Penerapan UU Nomor 28 Tahun 2014 Terhadap Perlindungan Hukum Atas Hak Cipta Lagu dengan Cover Lagu di Media Sosial - Ali Mufthi, Fikri; Kumala Sari, Nuzulia; Fahamsyah, Ermanto (WELFARE STATE Jurnal Hukum, 2024)
IIndonesian people are already familiar with music covers uploaded on social media. The formulation of the problem of this research is what laws include copyright for musical works on social media as well as copyright infringement on social media, what types of music are not commercial, as well as cover music that benefits the creator. The aim of this research is to understand the law regarding work copyright and its violations, the application of non-commercial music covers that comply with the provisions of the law and music covers that benefit music creators. The research methods used are doctrinal law and descriptive research. The type of data used is secondary data using library research methods. The analysis in this research is qualitative. Based on the results and discussion above, the activity of covering music on social media is considered a copyright violation because it violates the moral and economic rights of the creator or copyright holder, but if it is non-commercial in nature, this can be profitable for the music creator even if the song cover is from the original creator.